Glycerin levels for crossbred heifers supplemented in pasture: intake behavior - 10.4025/actascianimsci.v34i1.12520 - Mariana de Souza Farias; Robério Rodrigues Silva; Fernando Zawadzki; Carlos Emanuel Eiras; Beatriz Silva Lima; Ivanor Nunes do Prado (Acta Scientiarum. Animal Sciences, 2011)
The effect of glycerin inclusion on the intake behavior of heifers was analyzed. During the 102-day experimental period, thirty-six 13-month old heifers, average initial weight 226±12 kg, were distributed in a completely randomized design with four treatments and nine replications: G0.0 = control, G2.8 = 2.8%, G6.1 = 6.1%, and G9.1 = 9.1% glycerin in DM intake. Intake behavior was undertaken by monitoring animal activities for 24 hours every five minutes. The inclusion of glycerin in the diet resulted in a linear decrease in grazing time, linear increase in idle time and quadratic effect on trough time. Moreover, glycerin inclusion did not affect the number of grazing and rumination periods. The number of idle periods showed a quadratic effect, whereas trough period decreased linearly with increasing glycerin. Glycerin did not affect grazing time and rumination period. Idle time increased linearly with increasing glycerin in the diets. Time had a quadratic effect and feeding and total chewing time showed a linear decrease with glycerin inclusion in the diets